IVY plots and Gaussian interval plots. (21st March 2021) - Sarkar, Jyotirmoy; Rashid, Mamunur
Abstract: While a dot plot depicts data on a quantitative variable without distortion, a boxplot shows only the five‐number summary. For large data, to aid in counting, we propose an IVY plot as a companion to a dot plot. Also, for large data, if the variable is approximately normally distributed, as a companion to a boxplot, we propose a Gaussian interval plot that depicts the five‐number summary, the mean, the SD, the sample size, and the counts of outliers. We hope these enhanced visualizations will add value to the commonly used methods.